The value of emotional intelligence for high performance coaching - A commentary - Haime, J. (International Journal of Sports Science and Coaching, 2011)
One of the primary roles of a leader is establishing a positive emotional climate within their organization so individuals have a positive environment to perform well and maximize their talents. As a leader, one of the primary roles of a coach is to establish a positive emotional climate on the team and within the athlete. Without emotional intelligence this role cannot be executed effectively.